Physiological Response and Productivity of Indigofera Zollingeriana Mutant-2 After Salinity Stress with Different Defoliation - Muarif, A.P.; Nadir, M.; Syahrir, S. (Hasanuddin Journal of Animal Science (HAJAS), 2025)
ABSTRACT The cultivation of Indigofera zollingeriana is carried out using coastal areas to develop livestock farming, and the genetic structure of the plant can be altered through gamma irradiation technology to enhance the level of tolerance and resilience. Therefore, this research aimed to analyze the physiological response and productivity of Indigofera zollingeriana mutant-2 plant at several doses of gamma irradiation. A separate plot method was used based on a completely randomized design (CRD). The main plot comprised defoliation duration for 40 (B1) and 70 days (B2), while the subplot consisted of gamma irradiation with dose treatment description A1= Control, A2= 100 Gy, and A3= 200 Gy. Physiological parameters of the Indigofera zollingeriana plant consisted of leaf area, index, proline, chlorophyll, and stomata. Meanwhile, productivity parameters, there are dry matter, total leaf, total branch, and stem ratio, were examined using the analysis of variance. The physiological responses of chlorophyll and stomata parameters were also reported in relation to the dose of gamma irradiation (P<0.05) and age of defoliation (P<0.05), respectively. In this context, gamma irradiation treatment affected productivity, specifically in terms of dry matter (P < 0.05). The interaction between the doses had a significant effect on the total branch of Indigofera zollingeriana mutant-2 (P<0.05). The results showed that a dose of 200 Gy of gamma irradiation, with defoliation 70 days after uniform pruning, was the most effective in providing physiological responses and plant productivity. Indigofera zollingeriana, Irradiation, Defoliation Age, Physiology, Productivity